Surgical Site Infections in Saudi Arabia: A Review (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Surgical site infections (SSIs) are infections that occur postoperatively in the part of the body wherethe surgery took place. Methods: This study included searching PubMed for the keywords (SSIs rate) AND (SaudiArabia) from January 1, 2006, to July 1, 2021. Results: The rate of SSIs in Saudi Arabia was very low in somestudies (e.g. the rate was 0% in one of the studies) and high rate in other studies (e.g. the rate was 32.2% in one ofthe studies). The rate of SSIs in Saudi Arabia was dissimilar in different cities and for different types of surgeries.Conclusion: More researches are needed to study not only the rate of SSIs but also the associated risk factors tosupport the actions of the health team to reduce SSI occurrence and to decrease its complications if it is occurred.